Spiritual Leadership dan Emotional Intelligence Terhadap Organizational Citizenship Behavior: Peran Mediasi Workplace Spirituality dan Job Satisfaction - Jasman Saripuddin Hasibuan; Sri Fitri Wayhuni (JURNAL ILMIAH MANAJEMEN & BISNIS, 2022)
Purpose This study aims to examine the empirical work spirituality model, job satisfaction and organizational citizenship behavior of permanent lecturers at private Islamic Universities in North Sumatra.Methodology In this study, the sample size was 200 permanent lecturers from private Islamic universities in North Sumatra. Data collection techniques used are interviews, list of questions, and study documentation. The data analysis method used is the Structural Equation Model.Findings The results showed that Spiritual Leadership and Emotional Intelligence had a significant positive effect on Workplace Spirituality. Spiritual Leadership, Emotional Intelligence and Workplace Spirituality have a significant positive effect on Job Satisfaction. Spiritual Leadership, Emotional Intelligence, Workplace Spirituality and Job Satisfaction have a significant positive effect on Organizational Citizenship Behavior. The results show that Workplace Spirituality and Job Satisfaction are able to mediate the influence of Emotional Intelligence on Organizational Citizenship Behavior. The results also show that Job Satisfaction is able to mediate the influence of Workplace Spirituality on Organizational Citizenship Behavior.Originality/Novelty The research model uses five (5) variables and applies the concept of mediation, where each relationship in the research model is analyzed using by SEM-Lisrel.Implications This study has shown that Workplace Spirituality and Job Satisfaction have a mediating effect on the influence of Spiritual Leadership and Emotional Intelligence on OCB. Starting from the results of this study, the recommendation for further research is to try to analyze or use the variables of Workplace Spirituality and Job Satisfaction as independent variables, not as mediating variables.